Pendidikan Perempuan: Kajian Historis Timur Tengah dan Indonesia pada Masa Awal Islam dan Pra Kemerdekaan - Maulana, Rohasib (TAJDID, 2022)
Throughout the course of classical history, women were often discussed because of their discredited social status. The exoticism of women in the eyes of men is only limited to fulfilling biological needs, not having the value of social, economic, political, and educational authority both in the community and even in the family. The downturn was caused by the ignorance of pre-Islamic humans, before knowing the noble values ​​of Muhammad's treatise on the existence of women. This study tries to explore the history of women's education in the Middle East and Indonesia in the early periods, starting from the discussion of pre-Islamic women until the beginning of Islam coming and developing which then raised the status of women to become noble figures. This study is a library research, in the form of a study of the history of Islamic education in the Middle East and Indonesia, from the religious aspect to the social aspect of education. The results showed that pre-Islamic women were objects of violence and humiliation by misogynists. Hegemonic is wholly owned by men. The existence of women is considered not exotic and even considered to be unlucky, so they should be ostracized to the point of murder. It was only after Islam came that women got equal rights and authority with men from the social, economic, educational and even political aspects, so since then women have also received extensive educational services.